Tindak Wicara Pornografi - Soemitro, Herminie (Wacana, Journal of the Humanities of Indonesia, 2003)
This paper sugests the readers to be critical in their concern for the problem of pornography. It seems clear that pornography is a moral problem, but a simple argument from Traditional Philosophy of Language has shown that pornography does not have any meaning. This kind of argument is named Meta-ethics. However, pornography is a phenomenon in our society and it does happened. On the one side, we should resist the temptation of scrutinizing pornography as a moral problem. On the other side, pornography has risen a big worry in our society. In resisting the temptation we found a better theory, so that we are able to uncover the origin or pornography. John Langshaw Austin has saved some study of impossible phenomena including pornography by his theory of Speech Ary. The result of the study is that pornography is made possible in social relation and it is about Power.